Neutron tomography methods applied to a nickel-based superalloy additive manufacture build - Turner, R; Panwisawas, C; Lu, Y; Dhiman, I; Basoalto, H; Brooks, J (Elsevier, 2018)
Selective-laser melting (SLM) is one of the most rapidly developing and promising of all the so-called “Additive Manufacture” routes due to its capability to produce component geometries that would prove impossible using traditional manufacture. A selective-laser melting fabricated cuboid component was built using powder CM247LC, using standard methods, and this was subsequently analysed using neutron tomography methodology to allow for three-dimensional visualisation of the exterior and the interior of the component. The resulting neutron radiographs were processed and analysed for evidence of both porosity and grain boundary segregation within the component.